Comparing local transitions in Southern Europe: center-periphery relations and governors in the South of Spain and Portugal, 1970-1980 - Almeida, M. A.; Alberca, J. P. (Análise Social, 2020)
This article focuses on a comparative history of civil governors in Spain and Portugal, particularly on the role played by governors in the transitional processes in the South of each country. Two data bases of governors have been made available, one for Portugal and another for Spain. Our research pays special attention to governors’ political profiles and their relations with the central government and local powers. Eight Spanish provinces (Almería, Cádiz, Córdoba, Granada, Huelva, Jaén, Málaga and Sevilla) and five Portuguese districts (Beja, Évora, Faro, Portalegre and Setúbal) were analysed. Our conclusions emphasise the need to consider the local dimension to better understand democratisation processes.